Pengaruh Kualitas Layanan terhadap Kepuasan Mahasiswa dan Loyalitas Mahasiswa di Sekolah Tinggi Teknologi Jawa Barat - Iwan Juandi (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2018)
Development of Higher Education especially in Region Kopertis IV Jabar and Banten very rapidly so competition between universities is very tight. The more intense competition between universities, the higher education services should be more optimal so that the college won the competition. The aim of this research is to know the influence of the quality of the servants and the loyalty of students of West Java High School of Technology (STT Jabar in Bandung, West Java). Respondents in this research were students of High School Technology West Java (in Bandung, of West Java High school of Technology academic year is 2014 / 2015). The sample of this study did not distinguish all the majors, gender, area and religion the number of respondents in this study determined 46 respondents from the total number of students 84 by using sampling technique Sampling used in the form of simple random sampling method (simple random sampling). This research uses Path analysis and using help SPSS software program (Statistical Package For The Social). The results of this research there are indicate that: 1) the quality of service has a positive and significant effect on student satisfaction, 0.017 Signification is smaller than the 0.05 significance of t count 2,470 which states that ho rejected which means there is influence kualiats service to satisfaction. 2) satisfaction significantly influence loyalty student, 0.583 Significantly bigger than the 0.05 significance for t arithmetic 0,554 which states that ho received means that there is no influence between satisfaction with royalitas. 3) the quality of service has a positive and significant influence to student loyalty. It is suggested to the next researcher to extend the scope of the research to not only one type. STT Jabar should evaluate and improve service quality.